2021
DOI: 10.3390/dairy2040044
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Colostrum for Human Consumption—Improving Microbial Quality and Maintaining Bioactive Characteristics through Processing

Abstract: The main purpose of bovine colostrum, being the milk secreted by a cow after giving birth, is to transfer passive immunity to the calf. The calves have an immature immune system as they lack immunoglobulins (Igs). Subsequently, the supply of good quality bovine colostrum is required. The quality of colostrum is classified by low bacterial counts and adequate Ig concentrations. Bacterial contamination can contain a variety of human pathogens or high counts of spoilage bacteria, which has become more challenging… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 119 publications
(269 reference statements)
0
16
0
Order By: Relevance
“…There are about 250 or more functional compounds found in BC (Sienkiewicz et al 2021 ). The colostrum have immnunomodulating components and contributes to direct as well as indirect mechanism for adjusting the immune response of host (Fasse et al 2021 ). The food products prepared from cow colostrum contributes about 55.5% of global market in 2021 and the prognosis stipulated that there will be 6.4% increase per year of the colostrum products market from 2020 to 2030.…”
Section: Bioactive Compounds Of Colostrummentioning
confidence: 99%
See 3 more Smart Citations
“…There are about 250 or more functional compounds found in BC (Sienkiewicz et al 2021 ). The colostrum have immnunomodulating components and contributes to direct as well as indirect mechanism for adjusting the immune response of host (Fasse et al 2021 ). The food products prepared from cow colostrum contributes about 55.5% of global market in 2021 and the prognosis stipulated that there will be 6.4% increase per year of the colostrum products market from 2020 to 2030.…”
Section: Bioactive Compounds Of Colostrummentioning
confidence: 99%
“…The immunoglobulin contributes about 70–80% of total protein and present (30 to 200 g/L) which get declined to (0.4to1.0 g/L) shortly after parturition (McGrath et al 2016 ). The subclass namely IgG1 is responsible for accounting 75% antibody followed by other subcategories including IgM then IgA & IgG2 (Fasse et al 2021 ). The bovine trypsin inhibitor is responsible for protecting the growth factors.…”
Section: Bioactive Compounds Of Colostrummentioning
confidence: 99%
See 2 more Smart Citations
“…Lowtemperature colostrum (< 37˚C) itself can lead to diarrhea (Vallance and Finlay, 2000). In addition to animal studies, it has been reported in a recent human study that bovine colostrum can be useful in preventing and treating gastrointestinal diseases such as infectious diarrhea (Fasse et al, 2021). As noted above, attachment is an essential process in the pathogenicity of E. coli; thus, blocking bacterial attachment is a key factor in preventing bacterial overgrowth.…”
Section: Preventive Strategiesmentioning
confidence: 99%